Characterization of Two Novel mAbs Recognizing Different Epitopes on CD43 - Kim, Soseul; Hong, Jeong Won; Cho, Woon-Dong; Moon, Yoo Ri; Yoon, Sang Soon; Kim, Min-Young; Hong, Kwon Pyo; Lee, Yong-Moon; Yi, Jae Hyuk; Ham, Young Jun; Rah, Hyung Chul; Kim, Seung Ryul; et al. (Immune network, 2014)
JL1, a specific epitope on CD43, is a potential biomarker for the diagnosis of acute leukemia. Although qualitative assays for detecting leukemia-specific CD43 exist, there is a need to develop quantitative assays for the same. Here, we developed two novel monoclonal antibodies (mAbs), 2C8 and 8E10, recognizing different epitopes on CD43. These clones are capable of pairing with YG5, another mAb against JL1 epitope, because they were selectively obtained using sandwich ELISA. Antigens recognized by 2C8 and 8E10 were confirmed as CD43 by western blotting using the CD43-hFC recombinant protein. When expression on various leukemic cell lines was investigated, 2C8 and 8E10 displayed a disparity in the distribution of the epitope. Enzyme assays revealed that these mAbs recognized a sialic acid-dependent epitope on CD43. Using normal thymus and lymph node paraffin-embedded tissues, we confirmed a difference in the epitopes recognized by the two mAbs that was predicted based on the maturity of the cells in the tissue. In summary, we developed and characterized two mAbs, 2C8 and 8E10, which can be used with YG5 in a sandwich ELISA for detecting leukemia-specific CD43.